Bacterial cellulose gels, and methods for production and use
Cellulose-based gels with tunable properties are achieved by incorporating nanorods, ribbons, and fibers, addressing the limitations of existing gels in optical, thermal, and mechanical performance for advanced applications.
Patent Information
- Application Number
- JP2024124320
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2018-06-25
- Filing Date
- 2024-07-31
- Publication Date
- 2024-12-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing materials and methods for producing cellulose-based gels lack the ability to tune optical, thermal, and mechanical properties effectively, limiting their versatility and application in advanced technologies.
Development of cellulose-based gels containing cellulose nanorods, ribbons, and fibers, along with inorganic or polymer complexes, which can be formulated into hydrogels, organogels, aerogels, and liquid crystal gels with tunable optical, heat transfer, and stiffness properties, using methods that include alignment and crosslinking processes to achieve desired properties.
The resulting gels exhibit enhanced mechanical robustness, tunable optical anisotropy, and low thermal conductivity, making them suitable for applications requiring flexible and thermally insulating materials.
Smart Images

Figure 2024177160000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Application No. 16 / 017,319, entitled Bacterial Cellulose Gels, Methods of Making and Using, filed June 25, 2018. This application also claims the benefit of U.S. Provisional Application No. 62 / 684,661, entitled Nanocellulose Biofilms and Structural Gels for Thermal Insulation, filed June 13, 2018, the entire contents of which are hereby incorporated by reference in their entireties. [Background technology]
[0002] Federally sponsored research This discovery was made with government support under Grant DMR-1410735 awarded by the National Science Foundation and Grant DE-AR0000743 awarded by the U.S. Department of Energy. The Government has certain rights in this invention. Summary of the Invention
[0003] Cellulose-based flexible gels containing cellulose nanorods, ribbons, fibers, etc., and cellulose-enabled inorganic or polymeric composites. Composite materials are disclosed, where the gels have tunable optical, thermal transport, and stiffness properties. The gels disclosed are in the form of hydrogels, organogels, liquid crystal (LC) gels, and aerogels. Additionally, highly transparent and flexible cellulose nanofiber-polysiloxane composite aerogels are disclosed, characterized by enhanced mechanical robustness, tunable optical anisotropy, and low thermal conductivity. Additionally, gels comprising bacterially derived cellulose-based materials and methods of making and using bacterial cellulose gels are disclosed. [Brief description of the drawings]
[0004] [Figure 1]Schematic diagram showing the cellulose-enabled fabrication procedures for ordered gels: (a) cellulose nanomaterial aqueous dispersions, (b) hydrogels, (c) organogels, (d) aerogels, and (e) liquid crystalline gels. [Diagram 2] Transmission electron microscope (TEM) images of cellulose nanorods, nanofibers, and nanoribbons from various sources: (a) cellulose nanorods from cotton, (b) cellulose nanowires from cotton, (c) cellulose nanowires from wood pulp, and (d) cellulose nanoribbons from bacterial cellulose. [Diagram 3] Photographs of nematic cellulose (a) hydrogel, (b) organogel, (c) aerogel, (d) nematogel, and (e) scanning electron microscope (SEM) image of an ordered aerogel. Scale bars are 1 cm. [Figure 4] Photographs of cholesteric (a) cellulose-silica composition, (b) silica aerogel, (c) silica nematogel, and (d) SEM image of ordered silica aerogel. Scale bars are 5 mm. [Diagram 5] FIG. 1 is a schematic diagram of a spectrometer assembly that can be used for haze measurements with diffuse illumination and one-way field of view. [Figure 6] FIG. 1 is a general schematic diagram illustrating one embodiment of the production of the disclosed aerogels. [Figure 7] FIG. 1 shows the optical path of a typical pump-probe measurement system. [Figure 8] FIG. 1 shows the components of the hot box apparatus: an instrumentation box (simulating an internal temperature) on one side of the window sample; a control guard box surrounding the instrumentation box; a climate chamber box (simulating an external temperature) on the other side; and a sample frame that provides sample support and insulation. [Figure 9]Figures 9A-9C show various TEMPO-oxidized cellulose nanoparticle modifiers. Figure 9A shows surface modification with allylamine. Figure 9B shows surface modification with 2-(carbamoyloxy)-N,N,N-trimethylethanaminium adduct. Figure 9C shows surface modification with the example of methoxypolyethyleneglycolamine (mPEG-amine). [Figure 10] FIG. 1 illustrates the disclosed methods for generally forming polymethylsilsesquioxane (PMSQ) network cellulose hydrogels, organogels and aerogels. [Figure 11] 1 is a photograph showing the optical transparency of hydrogels formed by the disclosed methods. [Figure 12] 1 is a photograph showing the optical transparency of organogels formed by the disclosed methods. [Figure 13] 1 is a photograph showing the light transmission of aerogels formed by the disclosed method in which the surface modifier is allylamine. [Figure 14] 1 is a photograph of an aerogel formed by the disclosed method in which the surface modifier is m-PEG-amine having an average molecular weight of 5000 Daltons. [Figure 15] 1 is a photograph of an aerogel formed by the disclosed method in which the surface modifier is carbamoylcholine chloride. [Figure 16] FIG. 1 shows that carbamoylcholine chloride-capped TOCN-PMSQ aerogels exhibit hydrophobic surface properties. [Figure 17A] 17A-17C are transmission electron microscope (TEM) images of the disclosed aerogels at various magnifications. Figure 17A shows that the colloidal dispersion consists mostly of individualized TOCNs, each with a diameter Dc of about 5 nm and a length Lc of 1-2 μm. [Figure 17B] Figures 17A-17C are transmission electron microscope (TEM) images of the disclosed aerogels at various magnifications, and Figure 17B is a scanning electron microscope (SEM) image showing well-defined, uniform nanofibers with diameters of 10-15 nm formed by polysiloxane. [Figure 17C]Figures 17A-17C are transmission electron microscope (TEM) images of the disclosed aerogels at various magnifications, and Figure 17C is a scanning electron microscope (SEM) image showing well-defined, uniform nanofibers with diameters of 10-15 nm formed by polysiloxane. [Figure 18] 1 is a graph showing the visible transmittance of the disclosed aerogels. [Figure 19] 1 is a graph showing the haze ratio of the disclosed aerogels. [Figure 20] 1 is a graph showing that the PMSQ matrix causes TOCN-PMSQ aerogel to exhibit strong absorption at wavelengths between 6-20 μm, mainly due to the Si-0 bond. [Figure 21] FIG. 1 is a graph showing the measured thermal conductivity of TOCN-PMSQ aerogel versus sample porosity. [Figure 22] 1 is a graph showing a comparison of the thermal conductivity of aerogels formed from nanocellulose modified with carbamoylcholine chloride (a quaternary amine) and aerogels modified with allylamine. [Figure 23] 1 is a graph showing the compressive stress-strain relationship for TOCN-PMSQ aerogels containing 0.06 wt.% TOCN. [Figure 24] Figure 24A shows the reorientation of A. hansenii bacteria using the infrared laser beam of a laser trap, and Figure 24B shows the reorientation of A. hansenii bacteria using the infrared laser beam of a laser trap. [Diagram 25] Photograph of dark field microscopy showing A. hansenii bacteria producing cellulose fibers. [Figure 26] Shown is the A. xylinum bacterium that produces cellulose fibers. [Figure 27]Figure 27A is a photograph showing the effect on cellulose fibril thickness when 1.5% sodium carboxymethylcellulose is added to A. xylinum. In Figure 27A, the cellulose fibrils are visible. Figure 27B is a photograph showing the effect on cellulose fibril thickness when 1.5% sodium carboxymethylcellulose is added to A. xylinum. In Figure 27B, the fibril thickness is greatly reduced and the fibrils are not visible in the photograph. [Figure 28] Figure 1. Acetobacter cells showing multiple cellulose synthase enzymes extruding cellulose fibrils from the cell membrane. As the fibrils grow longer, hydrogen bonds between adjacent strands cause the fibrils to coalesce and produce ribbons. [Figure 29] Figure 1 shows an Acetobacter cell displaying multiple cellulose synthase enzymes extruding cellulose fibrils from the cell membrane. In this iteration, carboxymethylcellulose was added to the growth medium so that hydrogen bonds do not form the fibrils into fibrous ribbons. [Diagram 30] Figure 30A is a photograph showing an example of a disclosed aerogel biofilm, and Figure 30B is a photograph showing an example of a disclosed aerogel biofilm. [Diagram 31] Figure 31A is a thermal imaging photograph comparing a standard polysiloxane polymer to a gel formed by the disclosed method, and Figure 31B is a thermal imaging photograph comparing a standard polysiloxane polymer to a gel formed by the disclosed method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0005] As used herein, a "gel" is understood to be a substantially dilute crosslinked system that does not exhibit flow when in a steady state. The primary component of a gel is the surrounding ambient fluid, which may be in liquid or gas form. Prefixes such as "aero," "organo," "hydro," and variations are understood to indicate the surrounding fluid in the crosslinked gel matrix and the primary component of the gel material.
[0006] The disclosed gels contain cellulosic nanocomposites aligned in an ordered liquid crystal phase. Thus, the disclosed gels allow formulators to tailor the optical transmittance of the gel, thereby making the optical properties of the gel range from opaque to transparent. In addition, these properties can be tailored to interact with a wide range of the electromagnetic spectrum, for example, from the visible spectrum to the infrared spectrum. In one embodiment, the thermal conductivity of the gel can be tailored. The bulk properties of the disclosed gels, for example, the level of stiffness or flexibility, can be tailored by the selection of the constituent cellulosic materials, for example, nanorods, ribbons, fibers, etc., as well as the concentration of these materials in the resulting gel.
[0007] As used herein, "film" and variations refer to a non-porous lamella ranging in thickness from about 10 nm to 1 mm and any lateral extent. As used herein, the term "cross-section" refers to width, and these terms are used interchangeably. The disclosed cellulosic nanomaterials have widths of about 10 nm to about 500 nm. The length of the nanomaterial is at least 10 times its width.
[0008] The term "composition" as used herein refers to the disclosed cellulose nanomaterial aqueous dispersions, hydrogels, organogels, aerogels, and liquid crystal gels. The composition may be a single layer of material including the nanomaterial, or the composition may be formed from two or more separate layers, each layer being made of only one material. As a non-limiting example, one layer may be made of an ordered nematic cellulose gel, on which is provided a second layer of an aligned cholesteric cellulose film. The layers thus form an integrated composite with separate layers.
[0009] The term "hydrogel" as used herein refers to a network of cellulosic material as a colloidal gel dispersed in a carrier. In one embodiment, the carrier is water. In another embodiment, the carrier is a mixture of organic solvents that are compatible (miscible) with water. The cellulosic material can be crosslinked or non-crosslinked.
[0010] The term "organogel" as used herein refers to a gel in which the aqueous phase of a precursor hydrogel has been substantially free of all water and replaced with a water-compatible solvent. Non-limiting examples of compatible solvents include methanol, ethanol, propanol, and isopropanol. In one embodiment, the disclosed organogels have a two-dimensional crosslinked network. In another embodiment, the disclosed organogels have a three-dimensional crosslinked network.
[0011] The term "aerogel" as used herein refers to a gel resulting from further processing of the disclosed organogels described herein. The term "liquid crystalline gel" refers to compositions resulting from further processing of the disclosed organogels described herein.
[0012] The term "nanomaterial" refers to the disclosed cellulosic materials. The width of these materials is in the nanometer range, while the length of the cellulosic materials can vary from nanometer lengths to micrometers. The terms "nanomaterial," "cellulosic material," and "cellulosic nanomaterial" are used interchangeably throughout this disclosure.
[0013] The term "nematic" as used herein refers to a composition in which the disclosed cellulosic material possesses long-range orientational order. In addition, the cellulosic material is free-flowing and its center of gravity position is randomly distributed, yet still maintains its long-range orientational order. The disclosed nematic composition is uniaxial, having one axis that is longer and preferred, and the other two are equivalent.
[0014] The term "cholesteric" as used herein refers to a composition that has a helical structure and is therefore chiral. The disclosed cholesteric compositions are organized into layers with no positional order within the layer but with a director axis that varies with the layer. The variation in director axis may be periodic in nature. If present, the time of this variation (the interval to complete a full 360° rotation) is known as the pitch, which may be adjusted by the formulator, and the degree of pitch determines the wavelength of electromagnetic radiation that is reflected.
[0015] The abbreviation "TOCN" used throughout this specification means "TEMPO oxidized cellulose nanofibers." The term "low molecular weight compound containing a cationic moiety" refers to a compound having a moiety capable of reacting with oxidized cellulose carboxyl groups in addition to another cationic moiety. Non-limiting examples of units capable of reacting with oxidized cellulose carboxyl groups include hydroxyl groups, amino groups, thiol groups, etc. Non-limiting examples of cationic moieties include quaternary ammonium groups.
[0016] In one embodiment of the present disclosure, the composition comprises cellulosic nanoribbons aligned together, the orientation of which may be controlled by the formulator. The disclosed nanoribbons have an aspect ratio of about 1:100 to about 1:1000. In one embodiment, the disclosed nanoribbons may be used to form nematic soft gels.
[0017] These cellulose-based soft gels may include cellulose ribbons, fibers, and other component-particle structures with an aspect ratio of about 1:1000 in one embodiment. These soft gels are formed from interlocking cellulose particle networks within the material. The original cellulose solvent used to form the gel network may be retained or replaced to produce a variety of gel types, e.g., hydrogels, alcogels, aerogels, and liquid crystal gels. The use of the disclosed cellulose-based materials to form gel networks allows formulators to tailor the flexibility of the gel. This makes it possible.
[0018] The aspect ratio allows for a greater degree of flexibility or rigidity depending on the choice of cellulosic nanomaterial. Additionally, cellulose particles can be ordered by chemical and mechanical means to produce lyotropic liquid crystal dispersions with ordered phases. The ordering may be preserved during the crosslinking process to produce a variety of ordered gels, non-limiting examples of which are given above. Figure 1 shows the fabrication procedure for cellulose ordered gels.
[0019] In addition to flexibility, the optical transmittance of the disclosed gels can be tailored to range from opaque to transparent. The degree of opacity or transparency can also be tuned at any wavelength or range of wavelengths in the electromagnetic spectrum. These results can be obtained by adjusting various properties of the disclosed composites, i.e., the density or particle size distribution of the cellulosic nanomaterials. The addition of auxiliary components, such as liquid crystal materials, can also be used to adjust the optical properties of the disclosed composites.
[0020] An additional property that can be tailored to the needs of the formulator is the degree of thermal resistance exhibited by the gel. Several factors allow for tuning of thermal resistance: (1) the inherently low thermal conductivity of cellulose, (2) the dilution of fluid within the cellulose network, thereby regulating heat convection, and (3) the thermal conduction and convection properties of the fluid that comprises the cellulose-gel network.
[0021] In another embodiment of the present disclosure, the composition comprises aligned cellulose nanorods, the orientation of which may be controlled by the formulator. The disclosed nanoribbons have an aspect ratio of about 1:10 to about 1:100. In one embodiment, the disclosed nanorods can be used to form a composition having a cholesteric phase.
[0022] In one embodiment, the disclosed nanocrystals form ordered films, which may be ordered in a cholesteric phase in the film to form periodic structures, the pitch and pitch gradient of which are tunable for broadband Bragg reflection of incident electromagnetic radiation. In another embodiment, the resulting ordered gel is obtained due to the small relative aspect ratio of cellulose nanorods or similar nanomaterials, including nanocrystals. Nanorods produce a different phase than other nanomaterials, i.e., nanofibers. Due to this fact, broadband reflection is possible in ordered cellulose gels formed from cellulose structures with aspect ratios of about 1:10 to about 1:100.
[0023] Thus, mechanical flexibility, optical transmittance, and thermal resistance can be configured by adjusting the same parameters of the described nanofibers, except that these parameters currently refer explicitly to cellulose nanorods or other geometrically anisotropic cellulose structures.
[0024] Further aspects of the present disclosure relate to composite structures containing lamellae formed from the disclosed aerogels or liquid crystal gels. Composite structures with lamellae may be formed from the disclosed compositions containing nanofiber-like cellulosic materials (nematic phase) or from nanorod-like cellulosic materials (cholesteric phase). These composite structures include multiple layers.
[0025] In yet another aspect of the present disclosure, a composite structure in which an amount of cellulosic nanomaterial is replaced with one or more auxiliary materials that can affect the alignment of the composite nanomaterial. In one embodiment, a portion of the cellulosic nanomaterial is replaced with liquid crystals. Thus, nematic or cholesteric phase gels may have the liquid phase replaced by other anisotropic organic or inorganic materials. In one embodiment, silica is replaced with hydrogel. In another embodiment, a liquid crystal material, such as l-(trans-4-hexylcyclohexyl)-4-isothiocyanatobenzene, can replace the carrier of the hydrogel. In another embodiment, after incorporation and alignment of the non-cellulosic materials, the cellulose may be partially or totally removed by chemical means to produce gels and films with partial or total cellulose replacement.
[0026] In yet another embodiment of the present disclosure, the lamella comprises the disclosed composite structure. According to this embodiment, the lamella is formed from two or more separate layers, each layer comprising a different material. The cellulosic nanomaterial comprising each layer may further serve as a template and may be partially or entirely replaced by other materials, such as silica or other polymers.
[0027] Further disclosed are methods for producing composite structures. Exemplary methods may include preparing a mixture of growth medium, bacteria, and an additive that reduces the degree of (e.g., hydrogen) bonding between cellulose fibrils, producing a thin film of bacterial cellulose, exchanging the water contained within the thin film with a solvent, and drying the thin film to remove the solvent to form an aerogel. The additive may be a molecule that can reduce hydrogen bonding between fibrils in the growth medium (e.g., carboxymethylcellulose) and / or provide steric hindrance to the bonding between fibrils. Exemplary additives may include short molecules that make hydrogen bonds with cellulose fibrils (nanofibers) as they are created. The additive may be a charged or uncharged oligomer that can adsorb to cellulose by hydrogen bonding or other interactions.
[0028] Cellulose Nanomaterials The disclosed cellulose nanomaterials can have a variety of shapes and cross-sectional forms depending on the natural source of the nanomaterial and the process used to produce the particles. The disclosed cellulose nanomaterials can have shapes such as rods, fibers, ribbons, whiskers, etc.
[0029] The disclosed cellulose nanomaterials can be obtained by chemical or mechanical processing of various natural sources, such as cotton, softwood pulp, hardwood pulp, tunicates, and bacterial cellulose, etc. Typically, nanorods and nanofibers can be obtained from multiple sources, such as cotton and bacterial cellulose.
[0030] In one embodiment, the disclosed nanocellulose can have a length of about 10 μm to 100 μm and a cross-section of about 10 nm to 50 nm. In another embodiment, the disclosed nanocellulose can have a length of about 1 μm to 10 μm and a cross-section of about 3 nm to 10 nm. In yet another embodiment, the disclosed nanocellulose can have a length of about 100 nm to 1 μm and a cross-section of about 3 nm to 10 nm. FIG. 2 shows TEM micrographs of cellulose particles with the characteristic length scales of the above-mentioned embodiments: (a) 10 nm×200 nm cellulose nanorods obtained by chemical processing from cotton, (b) 7 nm×800 nm cellulose nanowires from cotton, (c) 4.8 nm×1 μm cellulose nanowires from wood pulp, and (d) 10 nm×50 nm×10 μm cellulose nanoribbons from bacterial cellulose.
[0031] Cellulose nanomaterials can be obtained by chemical hydrolysis of native cellulose with sulfuric acid, hydrochloric acid, etc., or by 2,2,6,6-tetramethylpiperidine-l-oxyl radical (TEMPO)-mediated oxidation. Alignment Method Cellulose nanomaterials show linear versus nematic or cholesteric ordering, respectively. Or circular shear may align the nanofibers. The nematic ordering of the disclosed cellulose nanofibers is shown in FIG. 1(b). In one embodiment, the cellulose nanomaterial dispersion can be confined between glass plates in a mold, and when a shear stress is applied from the plates in a specific direction, the individual nanocellulose particles align to form a unique director alignment across the confined dispersion. In another embodiment, the nanocellulose undergoes unidirectional alignment upon extrusion from a nozzle, syringe, or similar device of sufficiently small diameter. In the case of extrusion alignment, no confining plates are required, and the aligned dispersion takes the form of a thin bead with a linear extent much larger than its cross-sectional extent, on a supporting substrate or other structure. In yet another embodiment, the helical axis of the cellulose nanorods in the cholesteric phase may be aligned by counterclockwise circular shear during evaporation of the dispersion.
[0032] The disclosed cellulose nanomaterials may also be aligned by magnetic or electric fields. In one embodiment, the relative permeability magnetic anisotropy of cellulose nanomaterials may be utilized to induce uniform alignment of the nanocrystals. Under a sufficiently strong magnetic field (about 1 T), uniform alignment of the nanocrystals perpendicular to the magnetic field is achieved by the magnetic interaction of the induced magnetic dipole moment of the cellulose nanomaterial with the applied magnetic field. In another embodiment, an oscillating electric field may also be used to align the cellulose nanomaterial with its long axis along the electric field. Ordered hydrogels The alignment of the disclosed cellulose nanomaterial dispersion may be preserved upon its conversion to a hydrogel, example embodiments of which are shown in Figures 1(b) and 3(a). The degree of crosslinking of the cellulose nanomaterial establishes the degree to which uniform ordering is preserved in the dispersion. For example, a low level of crosslinking provides weaker gelation. Conversely, a greater degree of crosslinking produces a more rigid gelation. Gelation is accomplished by addition of acid, a photoacid generator to the uniformly ordered cellulose nanomaterial dispersion, and exposure to light, alcohol, or other cation exchange reagents. In one embodiment, hydrochloric acid, acetic acid, nitric acid, sulfuric acid, and phosphoric acid may be added to drive gelation. In another embodiment, Ca is added to provide crosslinking. 2+ may be added. Ordered organogels The disclosed ordered hydrogels can be converted to organogels using a solvent exchange method, as shown in Figure 1(c) and Figure 3(b). For example, the hydrogel can be immersed in a bath filled with ethanol while being gently shaken, and then the solvent can be replaced at regular intervals. In this way, water is sequentially removed from the matrix and replaced with ethanol. Other organic solvents can be substituted for ethanol. Non-limiting examples of other solvents include methanol, ethanol, isopropanol, butanol, hexane, acetone, dichloromethane, dimethylformamide (DMF), dimethylsulfoxide (DMSO), and toluene. Ordered aerogels or films The cellulose aerogels or films herein can be produced from the nanostructured organogels disclosed herein above. Exemplary aerogels are shown in FIG. 1(d) and FIG. 3(c). The resulting cellulose nanomaterial aerogels are porous, having a cellulose nanocrystal skeleton of about 0.1 to about 99.9% and a porosity of about 0.01 to about 99.99%. In one embodiment, the porosity is about 97% to about 99%.
[0033] Aerogels containing low percentages of nanocellulose-based material will yield aerogels with a high degree of transparency, e.g., from about 1% to about 50% by weight. Aerogels containing from about 50% to about 90% by weight of nanocellulose-based material will yield aerogels with a high degree of semi-transparent scattering.
[0034] Deformation and deformation of aerogel during drying due to surface tension and capillary pressure in the surrounding atmosphere To prevent crystallization and collapse, supercritical drying, freeze drying, or ambient drying with low surface tension solvents are used to remove the liquid solvent from the cellulose nanocrystal composites while maintaining the disclosed liquid crystal structures, e.g., nematic or cholesteric liquid crystal ordering.
[0035] As previously disclosed herein, the resulting monolithic cellulose nanomaterial film is a solid material of 100% cellulose composition. Ambient drying is used to remove the liquid solvent.
[0036] Ordered Liquid Crystalline Gels The cellulose LC gels disclosed herein may be produced from the disclosed nanostructured organogels. The organic solvent is replaced with LC by solvent exchange. In the case of LC gels, the LC acts as the solvent for the gel. Figure 1(e) shows a schematic of an LC gel, while Figure 3(d) shows an LC gel where the LC solvent is in the nematic phase. The disclosed compositions may include any LC as a solvent for the gel. Non-limiting examples of nematic LCs include: 1-(trans-4-hexylcyclohexyl)-4-isothiocyanatobenzene; 4'-(hexyloxy)-4-biphenylcarbonitrile; 4'-(octyloxy)-4-biphenylcarbonitrile; 4'-(pentyloxy)-4-biphenylcarbonitrile; 4'-heptyl-4-biphenylcarbonitrile; 4'-hexyl-4-biphenylcarbonitrile; 4'-octyl-4-biphenylcarbonitrile; 4'-pentyl-4-biphenylcarbonitrile; 4,4'-azoxyanisole; 4-isothiocyanatophenyl 4-pentylbicyclo[2.2.2]octane-1-carboxylate; 4-(trans-4-pentylcyclohexyl)benzonitrile; 4-methoxycinnamic acid; N-(4-ethoxybenzylidene)-4-butylaniline; and N-(4-methoxybenzylidene)-4-butylaniline.
[0037] Cellulose-templated ordered inorganic gels or films Inorganic nanomaterials may be incorporated into the previously disclosed ordered gels or films using cellulose nanomaterials as templates. As a non-limiting example, FIG. 4 shows a cellulose-enabled cholesteric (a) cellulose-silica film composition, (b) silica aerogel, and (c) silica LC gel, which is a LC with the solvent in its nematic phase. An SEM image of the ordered silica aerogel is shown in FIG. 4(d). In a final processing step, the cellulose nanomaterial may be removed to obtain the inorganic gel or film. Alternatively, the inorganic / cellulose composite gel or film is formed without etching the cellulose nanomaterial. As one non-limiting example, the inorganic gel or film is made of silica, organo-silica, titanium dioxide, aluminum oxide, rare earth oxides, etc. The weight concentration of the inorganic nanomaterial in the inorganic / cellulose composite may range from about 1% to about 99%.
[0038] Cellulose-templated ordered polymer gels or films Polymers may be incorporated into the ordered gels or films disclosed hereinabove using the cellulose nanomaterial as a template. In a final processing step, the cellulose nanomaterial may be removed to obtain a polymer gel or film. Alternatively, the polymer / cellulose composite gel or film may be formed without etching the cellulose nanomaterial. As one non-limiting example, the polymer gel or film may be made with phenol-formaldehyde, melamine formaldehyde, urea-formaldehyde, poly(acrylic acid), polyester, etc. The weight concentration of the polymer nanomaterial in the polymer / cellulose composite may range from about 1% to 99%.
[0039] Surface functionalization of ordered gels The surface properties of the disclosed gels can be modified by functionalizing the surface of the cellulose network. The disclosed aerogels without surface functionalization are hydrophilic and can dissolve or shrink in their total volume upon contact with water. Surface modifiers, such as dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride (DMOAP) and trichloro(lH,lH,2H,2H-perfluoro-octyl)silane, can be added to the hydrogel prior to conversion to an aerogel. This type of surface modification provides a stable hydrophobic aerogel upon exposure to water.
[0040] Ordered colloidal dispersions in gels Colloidal particles having lengths ranging from about 1 nm to 10 μm can be homogenously dispersed within the gel. In one embodiment, the colloids can include gold and silver plasmonic nanoparticles, such as rods, triangular platelets, and triangular frames; ferromagnetic nanoparticles, such as ferromagnetic nanoplatelets; quantum dots, such as nanospheres, -cubes, -rods, and the like. The colloidal particles are introduced into the cellulose before crosslinking occurs. As described herein above, crosslinking binds the colloidal inclusions to the ordered cellulosic network through interactions with colloid surface ligands. Any of the disclosed gels can contain one or more types of colloidal particles.
[0041] The disclosed gels have a thickness of about 1 μm to about 10 cm. In one embodiment, the thickness varies from about 10 μm to about 1 cm. In another embodiment, the thickness varies from about 100 μm to about 10 cm. In a further embodiment, the thickness varies from about 50 μm to about 1 cm. In yet another embodiment, the thickness varies from about 1 cm to about 10 cm. In yet another embodiment, the thickness varies from about 10 μm to about 100 cm. In yet another embodiment, the thickness varies from about 500 μm to about 10 cm.
[0042] The transmittance of the disclosed gels relates to the amount of electromagnetic radiation that is prevented from passing through the gel. 0% transmittance results in an opaque material that does not allow transmission. 100% transmittance results in a material that is transparent to electromagnetic radiation. The disclosed gels can have a transmittance of 0% to 100%. In one embodiment, the gel has a transmittance of about 5% to about 15%. In another embodiment, the gel has a transmittance of about 25% to about 50%. In yet another embodiment, the gel has a transmittance of about 95% to 100%. In yet a further embodiment, the gel has a transmittance of about 15% to about 35%. In yet another embodiment, the gel has a transmittance of about 50% to about 75%. In yet another embodiment, the gel has a transmittance of about 25% to about 75%.
[0043] The disclosed gels and composite materials have a viscosity of about 10 -3 In another embodiment, the thermal conductivity is about 10 -2 In yet another embodiment, the thermal conductivity is about 10 -1 In yet a further embodiment, the thermal conductivity is about 10 -3 In yet another embodiment, the thermal conductivity is about 10 -2 In yet another embodiment, the thermal conductivity is from about 1 W / (mK) to about 10 W / (mK).
[0044] The disclosed gel has a relative emissivity value of about 10 -2 The range is ~0.99. The disclosed gels and composite materials have a thermal conductivity of about 1 Pa to about 10 6 In one embodiment, the modulus of elasticity is from about 10 Pa to about 10 5 In another embodiment, the modulus of elasticity is about 10 2 Pa ~ about 10 6 In yet another embodiment, the modulus of elasticity is about 10 3 Pa ~ about 10 5In yet a further embodiment, the modulus of elasticity is from about 10 Pa to about 10 3 In yet another embodiment, the modulus of elasticity is from about 1 Pa to about 10 Pa. In yet another embodiment, the modulus of elasticity is from about 10 4 Pa ~ about 10 6 It is Pa.
[0045] procedure The cellulosic starting materials for the disclosed gels can come from a variety of sources. Surface-sulfuricated cellulose particles suspended in water (FIGS. 1(a) and 2) can be prepared by sulfuric acid-mediated oxidation of native cellulose. Surface-carboxylated cellulose nanofibers and nanoribbons suspended in water can be prepared by 2,2,6,6-tetramethyl-l-piperidinyloxy (TEMPO)-mediated oxidation of native cellulose. Dispersions of these nanomaterials spontaneously generate thermodynamically stable cholesteric (in the case of cellulose nanorods) or nematic (in the case of cellulose nanofibers or nanoribbons) liquid crystalline phases, which can be transformed into hydrogels with similarly ordered spatial structures of cellulose particles (FIGS. 1(b) and 3(a)).
[0046] The cellulosic starting material of the disclosed aerogels can be biosynthesized by Acetobacter xylinum, Acetobacter hansenii, or other examples of bacterial strains that utilize, for example, glucose as a carbon source. In one example, Acetobacter xylinum can be cultured under static conditions in glucose medium for 1-3 weeks to produce a cellulose thin film. To remove bacterial cell debris, the bacterial cellulose can be boiled in 1 wt.% aqueous NaOH solution for 2 hours, followed by washing with water and neutralization with 0.2% acetic acid.
[0047] The thus obtained native cellulose material can be easily decomposed into individual nanocrystals by controlled TEMPO-mediated oxidation. For example, 2 g of bacterial cellulose was suspended in water (150 mL) containing TEMPO (0.025 g) and NaBr (0.25 g). 1.8 M NaClO solution (4 mL) was added, and the pH of the suspension was maintained at 10 by adding 0.5 M NaOH. The reaction was terminated when no further decrease in pH was observed. The pH is then adjusted to 7 by adding 0.5 M HC1. The TEMPO oxidation products were cellulose nanorods with diameters of 4-10 nm and lengths of 1000-3000 nm, which were then thoroughly washed with water by filtration and stored at 4 °C.
[0048] Cellulose nanocrystals may also be synthesized from native cellulose by sulfuric acid hydrolysis. Aqueous suspensions of such cellulose nanocrystals above a critical concentration (about 3-6 wt.%) self-assemble into a liquid crystal structure, chiral nematic phase, which exhibits a periodic helical structure with a pitch that may be controlled in the range of 5-70 μm. This structure can strongly reflect electromagnetic radiation of wavelengths comparable to the pitch, and simultaneously serve as a highly efficient low emissivity structure by adjusting the pitch to be in the appropriate range. The disclosed films can have a pre-set gradient of cholesteric pitch within the helically ordered nanocrystal self-assembly, and can achieve broadband infrared selective reflection and low emissivity (compared to the red infrared emission curve taken from the solicitation), while being transparent in the visible spectral range and transmitting solar radiation in the near IR range (blue curve).
[0049] The concentration of the liquid crystalline cellulose nanocrystal dispersion was then adjusted to 3 wt.% and used for preliminary studies. The chiral nematic liquid crystal ordered nanocrystals were then poured into a mold where the orientation of the helix could be uniformly aligned perpendicular to the film plane using circular shear or a magnetic field. The polarized optical micrograph shown in Figure 4(c) was obtained for a sample with the helical axis aligned horizontally, providing a side view of the periodic helical structure of the chiral nematic liquid crystal. In the design and fabrication of the AIR FILM, this helical axis was set perpendicular to the plane of the film and along the window normal (Figure 2), which was achieved using the method of circular shear. (Park JH et al. “Macroscopic control of helix orientation in films dried from cholesteric liquid-crystalline cellulose nanocrystal suspensions”, ChemPhysChem. 15, 1477-1484, 2014).
[0050] After preparation of cellulose nanomaterials from one or multiple sources, the cellulose nanomaterials may be dispersed in water and aligned by the following methods. First, aqueous suspensions of cellulose nanorods above a critical concentration (approximately 0.1-4%) self-assemble into liquid crystal phases of nematic or cholesteric ordering. Second, linear or circular shear can be used for the nematic or cholesteric phases, respectively, to induce uniform alignment throughout the dispersion. In particular, the dispersion can be confined between glass plates in a mold such that when shear stress is applied from the plates in a specific direction (along a line or by rotation), the individual nanomaterial directors align to form a unique director alignment throughout the confined dispersion. As an alternative, but complementary, approach to dispersion alignment, the nanocrystals undergo uniform alignment upon extrusion from a nozzle, syringe, or similar device of sufficiently small diameter. In the case of extrusion alignment, the aligned dispersion takes the form of thin beads with a linear extent much larger than their cross-sectional extent, and no confining plates are required so that they remain on a supporting substrate or other structure. Furthermore, the relative permeability magnetic anisotropy of cellulose nanomaterials can be exploited to induce uniform alignment of the nanocellulose. Under a sufficiently strong magnetic field (~100 mT), uniform alignment of the nanocrystals is achieved by the magnetic interaction of the induced magnetic dipole moment of the cellulose nanomaterial with the applied magnetic field. (An oscillating electric field can be used to align the nanocellulose with its long axis along the electric field.) Aligned cellulose nanomaterial dispersions may be crosslinked to convert them into hydrogels while preserving their ordering. The degree of crosslinking of the cellulose nanomaterial chains establishes the degree to which uniform ordering is preserved within the dispersion; that is, for loosely crosslinked cellulose nanomaterials, weak gelation occurs; conversely, strong crosslinking produces rigid gelation. Gelation occurs as a result of the addition of acid, photoacid generators to the uniformly ordered cellulose nanomaterial dispersions and exposure to light, alcohol, or another cation exchange mechanism. Alternatively, cellulose nanorods, inorganic / cellulose nanorods, or polymer / cellulose nanorods can be self-assembled into a cholesteric phase by evaporation.
[0051] The nanocellulose-based ordered hydrogels were converted into organogels (Figures 1(c) and 3(b)) by gently rocking the cellulose-nanomaterial hydrogel in a bath filled with organic solvent while regularly replacing the solvent to encourage the exchange of water in the hydrogel with the organic solvent. In one example, the ethanol was replaced twice a day for 3 days to encourage total solvent exchange.
[0052] The disclosed cellulose aerogels (FIGS. 1(d) and 3(c)) may be produced from the nanostructured organogels disclosed herein above. The resulting cellulose nanocrystal aerogels are porous materials with a skeleton of about 0.1-99.9% cellulose nanocrystals and a porosity of about 0.1-99.9%. To prevent deformation and collapse of the aerogels during the drying step due to surface tension and capillary pressures in the ambient atmosphere, supercritical drying, freeze drying, or ambient drying with low surface tension solvents are used to remove the liquid solvent from the cellulose nanocrystal composites while maintaining the disclosed liquid crystal structures, such as nematic or cholesteric liquid crystal ordering.
[0053] The disclosed cellulose LC gels (FIG. 1(e) and FIG. 3(d)) may be produced from ordered nanostructured organogels, where an organic solvent is chosen that is fully miscible with the LC. The organogels are placed in a bath of LC above the boiling point of the organic solvent, whereby the organic solvent is heated to a temperature of 1000° C. It is replaced by LC which acts as a replacement solvent for the gel.
[0054] The disclosed cellulose-templated ordered inorganic and polymeric gels or films may be produced by mixing cellulose nanomaterials with a silica precursor or prepolymer and drying the composite in an ambient environment. The cellulose nanomaterials are then mixed with an acidic (silica) by either aqueous (for aerogels) or alkaline (for polymer aerogels) treatment The hydrogels may be further transferred to organogels, aerogels, and LC gels based on the methods described above.
[0055] Example 1 Ordered gels made from cellulose nanorods The method described by Revol and coworkers (J.F. Revol, H. Bradford, J. Giasson, R.H. Marchessault, DG Gray. Int. J. Biol. Macromol. 14, Colloidal suspensions of cellulose nanocrystals (CNCs) consisting of cellulose nanorods were prepared by controlled sulfuric acid hydrolysis of cotton fibers according to (170 (1992)). During this method, the disordered or paracrystalline regions of cellulose are preferentially hydrolyzed, while the crystalline regions, which have a higher resistance to the acid, remain intact. 7 g of cotton was added to 200 g of 65 wt% sulfuric acid and stirred in a water bath at 45 °C for up to several hours until the cellulose was completely hydrolyzed. The mixture was occasionally sonicated. This was found to be helpful in breaking down the amorphous cellulose regions. The cellulose suspension was then centrifuged at 9000 rpm for 10 min and redispersed in deionized water six times to remove excess sulfuric acid. The resulting precipitate was placed in a dialysis tube (MWCO 12000-14000, Thermo Fisher Scientific Inc.) in deionized water for 3 days until the pH of the water remained constant. The dimensions of the CNCs are approximately 5-10 nm in cross section and 100-300 nm in length on average. A 3 wt% CNC solution was then cast into a mold and allowed to evaporate under ambient conditions to obtain aerogels.
[0056] Example 2 Ordered gels made from cellulose nanofibers or nanoribbons Cellulose nanofibers (CNFs) with dimensions of 4.8 nm × several micrometers were prepared as described in the literature (T. Saito, M. Hirota, N. Tamura, S. Kimura, H. Fukuzumi, L. Heux and A. Isogai, Biomacromolecules, 10, 1992 (2009)). Briefly, cellulose-based, bleached coffee filters (1 g) were suspended in an airtight flask with 16 mg of 2,2,6,6-tetramethylpiperidine-l-radical (TEMPO) and 1.13 g of 80% sodium chlorite in 0.05 M sodium phosphate buffer (90 mL, pH 6.8). A 2 M sodium hypochlorite solution (0.5 mL, 1.0 mmol) was diluted to 0.1 M with the same 0.05 M buffer used as the oxidation medium and added to the flask in one step. The flask was immediately stoppered and the suspension was stirred at 500 rpm at 60 °C for 96 h. After the suspension was cooled to room temperature, the TEMPO-oxidized cellulose was thoroughly washed with water by filtration. A 0.1-1.0 vol.% aqueous dispersion of CNF was then poured into a mold, aligned by shear force, and a few drops of 1M HC1 solution were added to form a hydrogel after 2 h. The hydrogel was immersed in ethanol for 2 days for solvent exchange to form an organogel. To form a liquid crystal gel, the organogel was immersed in a bath of liquid crystal 4-cyano-4'-pentylbiphenyl at 90 °C for 12 h. Upon cooling to room temperature after that solvent exchange, the LC entered its expected nematic phase. Aerogels were produced by critical point drying of the organogel.
[0057] Example 3 Ordered gels prepared from cellulose nanorod-templated silica CNCs were synthesized according to the method in Example 1. 5 mL of 3 wt% CNC dispersion was then mixed with 10-75 μL of the silica precursor tetramethyl orthosilicate and stirred for 1 h. The composite was then placed in a Petri dish and dried for 1-2 days. The CNCs were then removed by pyrolysis (e.g., 540 °C, 20 h) or by keeping in 16% sodium hydroxide solution for 16 h. A silica hydrogel was formed. This may be further transferred to an organogel by solvent exchange or to an aerogel by critical point drying or ambient drying.
[0058] Example 4 Ordered gels made from cellulose nanorod-templated polymers CNCs were synthesized according to the method in Example 1. 5 mL of 3 wt% CNC dispersion was then mixed with 10-75 mg of water-soluble preformed polymer and stirred for 10 min. The composite was then poured into a Petri dish and dried for 1-2 days. The film was then cured at the polymerization temperature for 24 h. The CNCs were then removed with 16% sodium hydroxide solution for 16 h. A polymer hydrogel was formed. This may be further transferred to an organogel by solvent exchange or to an aerogel by critical point drying or ambient drying.
[0059] Light scattered as it passes through the aerogel can create a hazy appearance, which can result in reduced contrast of objects viewed through the film. Haze measurements can be made using a haze meter or a spectrometer. Figure 5 describes an apparatus that has been developed and adapted to measure the quality of the disclosed aerogels. The apparatus of Figure 5 has the advantage of making haze measurements that provide sensitive data regarding the cause of haze.
[0060] A typical setup includes an integrating sphere where the film to be measured is placed against a sphere entrance window. The interior surface of the integrating sphere is highly reflective over all visible wavelengths available from the light source. Light entering the integrating sphere reflects off the surface towards the film to be tested. The light transmitted through the film is then focused and directed towards a photodetector. The photodetector configured in the spectrophotometer can be computer driven to automatically calculate the transmittance and haze values. Haze can be determined by Haze = 100 x (Td / Tt), where Tt is the total transmittance which depends on the intensity of the incident light and the total light transmitted by the film, and Td is the diffuse transmittance which depends on the measurement setup and the light scattered by the film.
[0061] Morphological characterization of nanocellulose gels Characterization of the soundproofing can be performed by imaging of the nanoparticles using TEM and SEM. Figure 6 shows an outline of the procedure for probing the pore size, surface area, and structural properties of cholesteric cellulose-based aerogels under various preparation conditions. The ordering of the nanocrystals on a large scale will be probed using 3D imaging techniques such as Fluorescence Confocal Polarizing Microscopy (FCPM), Coherent Anti-Stokes Raman Scattering Polarizing Microscopy (CARS-PM), and Three-Photon Excitation Fluorescence Polarizing Microscopy (3PEF-PM). Furthermore, monitoring of the lateral uniformity of the disclosed liquid crystals and aerogels can be accomplished by using conventional dark-field, bright-field, and polarized optical microscopy. Spectroscopy in the visible and infrared ranges can also be utilized. Other properties of the disclosed aerogels include the mechanical properties (both the as-prepared aerogels and the encapsulated ready-to-install films), as well as the soundproofing and condensation resistance of the films installed on single-pane windows.
[0062] Measurement of thermophysical properties of aerogel Prior to application of the films to windows, the thermophysical properties (e.g., thermal conductivity, heat capacity) are characterized by optical pump-probe techniques to determine the type of film suitable for a particular application. This method uses a femtosecond laser to construct a high time resolution temperature measurement system. Figure 7 shows the optical path of a typical pump-probe measurement system. In the optical pump-probe method, sub-picosecond (ps) time resolution is possible by splitting the ultrafast sub-ps laser pulse output into an intense heating pulse, i.e., a "pump" beam, and a weaker "probe" beam, and controlling the optical path length difference between the pump and probe beams by a mechanical delay stage. The decay of the temperature rise is measured by the reflected energy of the probe pulse series. The thermal conductivity can then be estimated by fitting the temperature decay curve.
[0063] Condensation resistant After determining the thermal conductivity of the disclosed aerogels, the films can be applied onto windows to determine their thermal insulation and condensation resistance performance according to current standards of ASTM C1363-11 and ASTM C1199-14. This test method establishes the principles for the design of hot box apparatus and requirements for the determination of the steady-state thermal performance of windows when exposed to controlled laboratory conditions. The thermal insulation and condensation performance of a window is represented by the overall heat transfer coefficient U. Figure 8 discloses the components of the hot box apparatus: a measurement box on one side of the window sample (simulating the internal temperature); a controlled guard box surrounding the measurement box; a climate chamber box on the other side (simulating the external temperature); and a sample frame that provides sample support and insulation.
[0064] The walls of the hot box are insulated panels of plywood bonded to both sides of a solid layer of XPS insulation. The air conditioning system used for the meter box employs hydronic cooling and electrical resistance heating. Meter box cooling is measured using a high precision thermocouple in combination with a high precision flow meter to accurately quantify the heat removed from the meter box. Heat is added to the meter box via a PID-controlled electric heater. A high precision resistor circuit is employed to measure the heat added to the meter box. A constant and accurate temperature can be maintained and the total heat addition / removal can be measured. The hot box employs an insulated guard box surrounding the meter box and a hydronic guard loop is installed over the exterior of the meter box. The guard box minimizes the effects of temperature changes in the laboratory. The liquid guard loop further ensures that the exterior of the meter box remains at a constant temperature. An insulated baffle separates the air space from the mixing chamber of the meter box. The baffle plate is constructed using insulating material. For a 1 m x 1 m test window sample, at least 25 calibrated high precision thermocouples are used to measure the temperature of the baffle surface at 25 corresponding points in the air stream and at least 25 points on the inner surface of the test window sample. Air is drawn through the meter box baffle space at a rate typical of convection under real world conditions. DC powered axial draw circulation fans above and below the baffle are used to ensure smooth flow along the surface of the wall sample in the direction where convection occurs.
[0065] The climate box has the same dimensions and construction as the guard box. The climate side air baffle is constructed using the same materials and methods as the air baffle in the meter box. Heat is added to / removed from the climate box via four fan coils connected to a liquid chiller and hot water heater. Resistive heaters allow fine adjustment of the temperature, ensuring that the temperature remains near the set point for the duration of the test. The climate box has the capability to achieve realistic outdoor temperatures ranging from -30°C to 60°C. This allows the window assembly being tested to remain undisturbed when tested in climatic conditions ranging from cold to hot. The overall heat transfer coefficient is:
[0066]
number
[0067] (Where Q is the time rate of net heat flow W through the meter box opening, and A is the time rate of the meter Box opening area m 2 and T meter and T climate are the meter box and climate box temperatures, respectively) It is.
[0068] Cellulose-polysiloxane hybrid aerogel Further disclosed are transparent cellulose-polysiloxane hybrid hydrogels, organogels and aerogels, and methods for making the disclosed transparent cellulose-polysiloxane hybrid hydrogels, organogels and aerogels.
[0069] a) a cellulose matrix; b) a polysiloxane surface network; A cellulose-polysiloxane hybrid aerogel is disclosed comprising:
[0070] Without being limited by theory, these features are achieved by tightly controlling the dimensions of the nanofibers and the homogeneous gel skeletal network they form, which can be tuned to form an orientationally ordered liquid crystal (LC) state. In the gel fabrication method, an optimized acid / base catalyzed sol-gel reaction in a surfactant-based solution is used to form a polymethylsilsesquioxane (PMSQ) surface network.
[0071] Cellulose nanofibers with uniform diameter are first surface functionalized. This functionalization can employ small charged molecules or polymer grafting resulting in increased cellulose nanofiber stability. These nanofibers are then crosslinked with PMSQ fibers. In addition to their high optical transparency, superinsulation, flexibility and mechanical robustness, the disclosed hybrid aerogels may be made optically isotropic or anisotropic depending on the intended use by the formulator. In the case of anisotropic aerogels, these may be fabricated starting from the LC state of the colloidal dispersion of nanofibers. The resulting compositions may have practical applications since they have visible polarization, thereby allowing devices to be obtained that provide simultaneous thermal insulation while controlling visible light polarization.
[0072] Provided herein is a method for producing a silsesquioxane (PMSQ) network cellulose aerogel, comprising the steps of: a) contacting an aqueous dispersion of cellulose with an oxidation system that oxidizes the C6 hydroxyl units of the cellulose to carboxylate units to form an aqueous solution of oxidized cellulose nanofibers; b) reacting the oxidized cellulose nanofibers with a surface modifier to form an aqueous solution of surface-modified cellulose nanofibers; c) contacting the surface-modified cellulose nanofibers with polymethylsilsesquioxane (PMSQ) to form an aqueous polysiloxane precursor; d) hydrolyzing the polysiloxane precursor in the presence of an acid catalyst to form a PMSQ network cellulose hydrogel; e) exchanging the water contained in the hydrogel with a volatile solvent to form an organogel; f) removing the volatile solvent to form an aerogel; A method is disclosed that includes:
[0073] In one embodiment, the oxidation system comprises: a) Mixture of (2,2,6,6-tetramethylpiperidin-l-yl)oxyl (TEMPO) and NaClO Includes.
[0074] Modifier In one embodiment, the surface modifier is selected from C1-C6 linear or branched, saturated or unsaturated alkylamines, low molecular weight compounds containing cationic moieties, oligomers or polymers.
[0075] C1-C6 linear or branched, saturated or unsaturated alkylamines react with the carboxyl units of cellulose under the conditions of the present method to form carboxylate-quaternary ammonium complexes, for example as shown in Figure 9 A. One example of this embodiment involves the use of allylamine as a modifier.
[0076] Another embodiment includes the use of an oligomer or polymer as the modifier. In one iteration, m-PEG-amine with an average molecular weight of about 2000 to about 10,000 Daltons is used to modify the surface of the oxidized cellulose nanofibers. In one non-limiting example of this iteration, the modifier is m-PEG-amine with an average molecular weight of 5000 Daltons. For example, the subscript n is approximately 112 in the m-PEG-amine shown in FIG. 9C. Any oligomer or polymer capable of covalently binding to the surface carboxylates of the oxidized nanofibers can be used to modify the cellulose surface.
[0077] Further embodiments include modifier units that are low molecular weight compounds that contain cationic moieties. The molecular weight of this type of compound is less than about 400 g / mol. A non-limiting example of this embodiment is depicted in Figure 9B, where the use of carbamoylcholine salts is the modifier. The salts can be chlorine, bromine, etc.
[0078] General Procedure The nanocellulose concentration must exceed a critical concentration for spontaneous nematic ordering of the nanofibers to occur. This behavior offers formulators a unique opportunity to impart LC ordering at low TOCN volume fractions, providing a means to obtain the disclosed optical anisotropy and other properties.
[0079] Raw cellulosic materials obtained from natural sources can be used to produce the disclosed hydrogels, organogels and aerogels. For example, cellulosic materials such as cotton, grains, and paper products made from natural sources can be first oxidized at the C6 sugar carbons, thereby oxidizing -CHOH moieties to carboxylate moieties -COOH.
[0080] The oxidized cellulosic material is then treated with a modifier that allows the cellulose nanofibers in the hydrogel to remain aligned and unreactive to subsequent treatment with a networking agent. After treatment with the modifier, the nanofibers are then treated with methyltrimethoxysilane (a networking agent), which is hydrolyzed under acidic conditions to form a polysiloxane network throughout the hydrogel. Gelation results in a highly transparent monolithic hydrogel of functionalized TOCN crosslinked by a network of isotropic bicontinuous polysiloxane nanofibers.
[0081] Water is removed from the hydrogel by exchange with a volatile organic solvent to give the corresponding organogel. The resulting organogels exhibit both isotropic and liquid crystalline ordering, which can be controlled by adjusting the concentration of the surface-modified TOCNs. These orientationally ordered self-assembled structures are locked in place by the formation of a polysiloxane network. The disclosed method preserves the small and uniform cross-section of the individual fibers and their networks, and, as a result, ensures low light scattering.
[0082] The corresponding aerogels are formed by drying of the organogel, which can be shaped according to the formulator's needs. In addition to mechanical flexibility and robustness, many practical aerogel applications may require a high degree of hydrophobicity (e.g., to ensure that these aerogels are stable under ambient conditions and in humid environments).
[0083] Example 5 PMSQ network cellulose aerogel The disclosed cellulose nanofibers are produced through oxidation of native cellulose by selective modification of the C6 primary hydroxyl groups on the surface of native cellulose to TEMPO-catalyzed carboxylate groups under mild pH aqueous conditions. Nanofibers with diameters of 4.8 nm and micrometer-scale lengths are stabilized in basic solutions by Coulombic repulsion that overcomes the tendency of the anionic carboxylate moieties to form hydrogen bonds. As a result, aqueous TOCN dispersions are highly transparent. To eliminate the strong light scattering often observed in polymeric fibrous aerogels, which is attributable to the bundling and bunching of TOCNs that are uncontrollably cross-linked by direct hydrogel bonds, the inventors instead cross-link TOCNs with polysiloxane. This technique produces a uniform nanofiber network that exhibits a small scattering cross-section by preventing direct contact between TOCNs. Hydrolysis of the polysiloxane precursor is catalyzed by acid. However, even in weakly acidic conditions and dilute concentrations, TOCNs tend to form gel-like phases due to hydrogen bonding between carboxylic acid functional groups. To stably disperse TOCNs in polysiloxane precursor solutions, we implement various TOCN surface functionalization schemes, as shown in Figures 9A-9C.
[0084] TEMPO-mediated oxidation of cellulose produces a large density of carboxylic acid groups (~0.8 mmol / g) on the surface of nanofibrillated cellulose that can be used for surface modification. This provides a means to modify the physisorption properties of cellulose nanoparticles by covalently attaching either low molecular weight cationic molecules or polymer chains to the surface, thereby generating TOCNs stabilized by electrostatic repulsion or steric hindrance.
[0085] In one embodiment, shown in Figure 9A, the modification is affected by the physisorption of one or more polyelectrolyte monomers, in this example allylamine, to the anionic carboxylate groups of the oxidized cellulose, a process that does not significantly affect the cross-sectional diameter of the TOCNs due to the size of the low molecular weight cationic small molecules.
[0086] In another embodiment shown in Figure 9B, surface functionalization is accomplished by reaction of carboxyl groups with cationic amine-containing adducts. Figure 9B shows the reaction of 2-(carbamoyloxy)-N,N,N-trimethylethanaminium (choline carbamate) with TOCN. This reaction introduces another form of cationic charge electrostatic repulsion.
[0087] In yet another embodiment, shown in Figure 9C, the surface of the TOCN is modified by reaction with a polymeric material, in this example methoxypolyethyleneglycolamine (mPEG-amine). Grafting of this type of polymer provides a means of improving colloid-TOCN stabilization.
[0088] Functionalization of the TOCNs produces a cellulose matrix that is stable to treatment with polysiloxanes in later steps of the disclosed method. FIG. 10 illustrates the method generally. Oxidized and surface-modified cellulose nanofibers in aqueous suspension are represented by long aligned fibers, with differently shaded dots representing water and PMSQ molecules (leftmost diagram). The center diagram illustrates steps (c) and (d) of the method, where the nanofibers are first contacted with PMSQ, which is then hydrolyzed to produce a PMSQ network cellulose hydrogel. The resulting product of steps (e) and (f) is depicted as the resulting aerogel in the rightmost diagram. The resulting aqueous colloidal dispersions of transparent surface-modified TOCNs may exhibit LC ordering depending on the volume fraction of nanofibers in the colloidal dispersion. In addition, these solutions may exhibit birefringence when observed between cross-polarizers, as shown in FIG. 10.
[0089] Surface modification of TOCN 1. Cationic surface physical adsorption The surface of the TEMPO-oxidized cellulose nanofibers was then functionalized by physical adsorption of allylamine onto the nanofibers. 500 mg of 0.2 wt.% aqueous nanofiber solution was diluted with 2 mL of distilled deionized water and combined with 10 mg of allylamine. The mixture was stirred overnight and dialyzed for 2 days in a deionized water bath through a cellulose acetate membrane with a molecular weight cutoff of 12,000-14,000 g / mol to obtain the desired allylamine-TOCN. 2. Charged Small Molecule Modification The aqueous TOCN dispersion (500 mg of 0.38 wt.%) was diluted with 2 mL of deionized water followed by the addition of 24 mg of 1-[bis(dimethylamino)methylene]-1H-1,2,3-triazolo[4,5-b]pyridinium 3-oxide hexafluorophosphate (HATU), 20 μL of N,N-diisopropyl-ethylamine (DIPEA) and 50 mg of carbamoylcholine chloride and 40 μL of dimethylformamide (DMF). The mixture was stirred for 2 days and dialyzed for another 2 days to obtain the desired dispersed surface-modified nanofibers. 3.Oligomer / polymer modification The aqueous TOCN dispersion (500 mg of 0.2 wt.%) was diluted with 2 mL of DI water and then mixed with 28 mg of HATU, 20 μL of DIPEA, 18 mg of mPEG-amine (MW=5000) and 40 μL of DMF. The mixture was stirred for 2 days and then dialyzed for another 2 days to finally obtain mPEG-TOCN. All of the functionalized TOCN dispersions were concentrated to the desired concentration on a rotary evaporator. Preparation of PMSQ network cellulose hydrogels The disclosed PMSQ network cellulose hydrogels were fabricated by crosslinking functionalized TOCN with polysiloxane. For example, typically, 0.4 g of cetyltrimethylammonium bromide (CTAB) and 3.0 g of urea were dissolved in 8 mL of deionized (DI) water by sonication until the sol became homogenous. To this solution, 2 mL of functionalized surface-modified TOCN with different concentrations, 1–5 mL of methyltrimethoxysilane (MTMS) and 0.01 mmol of acetic acid were added under vigorous stirring. After stirring each sample for 30 min at room temperature, the sol was degassed in a vacuum oven and then transferred to a 5 cm diameter polystyrene Petri dish, sealed for gelation, and aged in a 60 °C oven for 3 days to form the desired hydrogel. Preparation of PMSQ network cellulose aerogels The hydrogels produced above were removed from the Petri dish and immersed in DI water for 24 h to remove urea and residual CTAB. This was followed by a solvent exchange at 60 °C for 2 days with isopropanol replaced every 12 h. Finally, CO2 supercritical drying was performed at 38 °C and 8.6 MPa to obtain the aerogel samples dried in a critical point dryer. This resulted in a yield of 30–200 μg / cm2 depending on the amount of MTM added to the functionalized surface-modified cellulose in the above step. mg / cm 3 Aerogels having bulk densities in the range of 69 mg / cm3 were obtained in one embodiment. 3 Aerogels having a density of 100 nm to 150 nm result in optimal optical transmission and mechanical flexibility. In one iteration of the disclosed method, no stress is introduced into the TOCN-PMSQ aerogels during the process.
[0090] FIG. 11 is a photograph showing the optical transparency of a hydrogel formed by the disclosed method. The hydrogel is a highly transparent monolithic hydrogel crosslinked by an isotropic bicontinuous polysiloxane nanofiber network as described herein. The hydrogel is included within the area enclosed by the dashed line. FIG. 12 is a photograph showing the optical transparency of an organogel formed by the disclosed method. The organogel is included within the area enclosed by the dashed line. FIG. 13 is a photograph showing the optical transparency of an aerogel formed by the disclosed method where the surface modifier is allylamine. The aerogel is included within the circle. FIG. 14 is a photograph of an aerogel formed by the disclosed method where the surface modifier is m-PEG-amine having an average molecular weight of 5000 Daltons. The circular aerogel is placed over a copy of the text. As can be seen in the photograph, the aerogel is transparent with no discoloration or distortion of the text. FIG. 15 is a photograph of an aerogel formed by the disclosed method where the surface modifier is carbamoylcholine chloride. The circular aerogel is placed over a copy of the text. Aerogel is transparent in that it does not discolor or distort text.
[0091] As shown in Figure 16, the carbamoylcholine chloride capped TOCN-PMSQ aerogels exhibit hydrophobic surface properties with a typical contact angle of 148°, mainly due to the presence of hydrophobic methyl groups on the polysiloxane fibers within the nanostructured aerogels. One advantage of the disclosed method is that no post-synthesis hydrophobization treatment is required when the disclosed gels are used in hydrophobic applications.
[0092] The optical and electronic imaging and spectral properties of the disclosed aerogels were analyzed. For both polarized and unpolarized bright-field optical microscopy imaging, an Olympus BX-51 polarized optical microscope was equipped with 10×, 20×, and 50× air objectives with numerical apertures NA=0.3-0.9 and a 0.5× tube lens mounted just before a CCD camera Spot 14.2 ColorMosaic (Diagnostic Instruments, Inc.). Transmission spectra were studied using a spectrometer USB2000-FLG (Ocean Optics) mounted on the microscope. For optical transmittance and haze measurements of the aerogels, a UV-VIS-NIR spectrometer (UV-3l0lpc, Shimadzu) with a range of 190 nm to 3200 nm equipped with a LabSphere brand integrating sphere accessory was employed. Haze is defined as the ratio of diffuse transmission to total transmission, and diffuse transmission is defined as the transmitted light separated by more than 5° from the direction of the incident light. Wavenumber 400 cm -1 ~4000cm -1 Infrared transmission spectra (wavelengths 2.5 μm–25 μm) were recorded on a Fourier transform infrared (FTIR) spectrometer (Nicolet AVATAR 370 DTGS, Thermo) equipped with an integrating sphere (NIR IntegratIR, Pike). Photographs of the samples were taken using a digital camera. IR thermographs were obtained with an IR camera (T630sc, FLIR). TEM images were obtained using a CM100 microscope (FEI Philips) at 80 kV. TOCN samples were negatively stained with phosphotungstic acid to increase imaging contrast: 2 μL of sample was drop-cast onto a formvar-coated copper grid and left to dry before immersing in the staining solution (aqueous 2 wt.% phosphotungstic acid). The porous morphology of TOCN-PMSQ was characterized using SEM with a Hitachi Su3500 and Carl Zeiss EVO MA 10 system. For this, a thin layer of gold was sputtered onto the freshly cut surface of the TOCN-PMSQ aerogel and observed under SEM at a low voltage of 5 kV (optimized to avoid distortion of the aerogel sample).
[0093] 17A-17C are transmission electron microscope (TEM) images of the disclosed aerogels at various magnifications. FIG. 17A shows that the colloidal dispersion is mostly composed of individualized TOCNs, each with a diameter Dc of about 5 nm and a length Lc=1-2 μm. FIGS. 17B and 17C are scanning electron microscope (SEM) images showing well-defined, uniform 10-15 nm diameter nanofibers, which are TOCN fibers formed by polysiloxane treatment and individually dispersed within the aerogel, as well as the narrow pore size distribution of the resulting porous network. The aerogel samples shown exhibit a 3D bicontinuous network-like structure, in which both the smooth gel framework and the pores are interconnected without aggregation or clustering. The example shown in FIGS. 17A-C has a weight / volume ratio of 69 mg / cm for the sample. 3 The bulk density ρ is calculated as b Then, ε = (l-ρ b / ρ s The porosity, defined as ρ ) × 100%, is determined to be approximately 94.9%, where ρ s is 1.35g / cm 3 is the skeletal density, which is assumed to be 100 nm. The average pore size for this particular example is calculated to be approximately 100 nm, in agreement with that observed directly from the SEM images. The mesoscale morphology of the 2.0 mm thick QA-capped TOCN-PMSQ composite aerogels with ultra-fine fibers and uniform pore size distribution produces hydrogels and organogels with very high optical transmittance of over 90% as well as aerogels with visible transmittance approaching 90% at 600 nm, as shown in FIG. 18.
[0094] The haze of the exemplified aerogel, defined as the ratio of diffuse transmittance to total light transmittance, was determined to be equal to 8.4%. Figure 19 is characterized according to the ASTM D1003 standard using an integrating sphere setup and integrated over the visible range (390-700 nm) shown in Figure S1. The PMSQ matrix causes the TOCN-PMSQ aerogel to exhibit strong absorption at wavelengths between 6 and 20 μm, primarily due to the Si-0 bonds in Figure 20. This provides formulators with the opportunity to independently control the transmission of visible and infrared light in embodiments where control of solar gain and emissivity is important, i.e., smart window applications.
[0095] The thermal, mechanical, and durability properties of the disclosed aerogels were analyzed. Thermal conductivity is measured by measuring both the heat capacity and thermal diffusivity of the aerogel samples. The heat capacity of the aerogels is measured by differential scanning calorimetry (DSC 204 Fl Phoenix, Netzsch). The thermal diffusivity of the aerogels is characterized by a laser flash instrument (LFA 457, Netzsch). Briefly, a light source heats one side of the material instantaneously, and the temperature increment of the other side of the material is recorded by infrared thermography for easy non-invasive temperature sensing. To suppress direct heating of the detector by the laser light, the top and bottom of the aerogels were covered with highly conductive carbon tape to prevent the laser from penetrating the sample. The thermal conductivity of the aerogels can be calculated by subtracting the contribution of the carbon tape from the effective thermal conductivity of the sandwich structure, which was determined by performing measurements on samples of different thicknesses. An Instron 5965 material testing system was used to study the mechanical properties and determine the stress-strain relationship. The mechanical properties shown in Fig. 4f were measured on TOCN-PMSQ aerogel samples with TOCN capped with 0.25 vol.% QA cut into rectangular strips of 20 mm × 6 mm × 1 mm. The aerogel durability tests were conducted under a 500-watt mercury lamp (Sun System 5, Sunlight Supply Inc.) for 24 h in a Tenney environmental test chamber maintained at 80 °C and 80% relative humidity.
[0096] Figure 21 shows the measured thermal conductivity of TOCN-PMSQ aerogels versus sample porosity. Figure 22 shows a comparison of thermal conductivity between aerogels formed from nanocellulose modified with carbamoylcholine chloride (a quaternary amine) and aerogels modified with allylamine. Figure 23 shows the compressive stress-strain relationship for TOCN-PMSQ aerogels with 0.06 wt.% TOCN. Bacterial cellulose Disclosed herein are cellulose (e.g., nanocellulose) biofilms derived from bacterial cellulose. The disclosed biofilms are suitable for use in producing thermal insulation and structural gels. Non-limiting examples of cellulose-producing bacteria that can be used to provide the disclosed biofilms include Acetobacter hansenii and Acetobacter xylinum.
[0097] Bacterial biofilms are generated in situ, for example, as shown in Figures 6, 9A-9C, and 10. The resulting cellulose gel can be ordered in orientation, for example, with oils such as silicone oils and / or with external stimuli such as infrared laser beams. Using an infrared laser beam as a laser trap, bacteria can be moved, reoriented, and positioned adjacent to one another, and the resulting fibrils of cellulosic material can coalesce with one another.
[0098] The disclosed cellulose gels can be ordered in orientation due to the alignment of the fibrils as they are produced due to hydrogen bonding between the fibrils. This results in the fibrils forming ribbons. Furthermore, by altering the growth nutrients, the number density of the fibrils within the bundles, and therefore the ribbons, can be determined by the formulator. Additionally, altering the bacterial culture can result in changes in fibril diameter.
[0099] Thus, modifications to the growth medium and nutrient composition, as well as variations in bacterial species, may be used to adjust the resulting gel to be transparent or opaque, flexible or rigid, thermally insulating or conductive, and brittle or load-bearing. The resulting gel may be further chemically treated to adjust the material and thermal properties of the invention, such as crosslink density, material composition, and hydrophobicity. Colloidal inclusions can be introduced into the resulting gel to adjust the optical, thermal, magnetic, and electrical properties of the gel.
[0100] Figures 24A and 24B show the reorientation of A. hansenii bacteria using the infrared laser beam of a laser trap. The laser trap may be used to move the bacteria to a position in the growth medium that provides easier harvesting of the film or to determine the density of the film. Figure 25 is a dark field microscope photograph showing A. hansenii bacteria producing cellulose fibers. The cellulosic material is visible as various single strands of cellulose coalesce into ribbons. This is shown diagrammatically in Figure 28. Figure 26 shows A. xylinum bacteria producing cellulose fibers.
[0101] Figures 27A and 27B show the effect of cellulose fibril thickness when 1.5% sodium carboxymethylcellulose (CMC) is added to A. xylinum. In Figure 27A the cellulose fibrils are visible. In Figure 27B the fibril thickness has decreased so much that the fibrils are no longer visible / photoresolvable. This is shown diagrammatically in Figure 29.
[0102] Once the film is produced, the bacteria may be killed using any suitable technique, such as the use of a basic solution, starvation, UV light, heat, toxins, plasma or other irradiation treatments, asphyxiation, and the like.
[0103] Example 6 Bacterial cellulose from A. hansenii is used in this example. The bacterial cellulose film is first purified by washing in 1 wt% aqueous NaOH at 70°C for about 4 hours to kill any remaining bacteria. The film is then transferred to DI water at 70°C or room temperature to remove excess NaOH and reduce the ionic strength to closer to that of pure DI water. Heating to 70°C accelerates the process, but the process also works equally well at room temperature (RT). The thin film is washed two more times with pure DI water (at RT or with gentle heating, e.g., to 70°C) for a total of three DI water rinses. The thin film is then transferred to pure isopropanol (IPA) and undergoes solvent exchange. This water to IPA solvent exchange can be performed at RT or 60°C depending on the urgency and desired rate. The thin film is then placed in a fresh bath of IPA to further dilute any water remaining in the solvent exchange bath. The number of times the thin film is washed with fresh IPA depends on the film thickness. For example, a thin film may require only two total IPA baths to adequately remove the water, while a thicker film may require 3-5 exchange cycles with IPA. After the water / IPA solvent exchange is complete, the thin film is dried by conventional critical point drying (CPD) techniques (using the same liquid CO2 that dried the aerogel). The pressure is bled off at about 50 PSI / min at the CO2 critical point, yielding the bacterial cellulose aerogel.
[0104] Figure 28 is a depiction of an Acetobacter cell showing numerous cellulose synthase enzymes extruding cellulose fibrils from the cell membrane. As the fibrils grow longer, hydrogen bonds between adjacent strands cause the fibrils to coalesce and form ribbons.
[0105] Figure 29 is a depiction of an Acetobacter cell showing multiple cellulose synthase enzymes extruding cellulose fibrils from the cell membrane. In this iteration, carboxymethylcellulose (CMC) is added to the growth medium, resulting in hydrogen bonds that do not form the fibrils into fibrous ribbons.
[0106] Figures 30A and 30B show the optical and mechanical properties of the disclosed aerogels prepared from bacterial cellulose. In Figure 30A, the aerogels are opaque, while Figure 30B shows the flexibility of the corresponding aerogels.
[0107] Example 7 Bacterial cellulose from A. hansenii with 1.5% carboxymethylcellulose added to the culture medium was used in this example. The bacterial cellulose film is purified by first washing in 1 wt% aqueous NaOH at 70° C. for about 4 hours to kill any remaining bacteria. The film is then transferred to DI water at 70° C. or room temperature to remove excess NaOH and reduce the ionic strength to approach that of pure DI water. Heating to 70° C. accelerates the process, but the process can also be performed at room temperature (RT). The film is washed two more times with pure DI water (at RT or with gentle heating, e.g., to 70° C.), for a total of three DI water rinses. The film is then transferred into pure isopropanol (IPA) and subjected to solvent exchange. This water-to-IPA solvent exchange can be performed at RT or 60° C. depending on the urgency and desired speed. The film is then placed in a fresh bath of IPA to further dilute any water that remains. The number of times the film is washed with fresh IPA depends on the thickness of the film. For example, thin films may require only two total IPA baths to adequately remove the water, while thicker films may require 3-5 exchange cycles in IPA. After the water / IPA solvent exchange is complete, the film is dried by conventional critical point drying (CPD) techniques (using the same liquid CO2 that dried the aerogel). At the CO2 critical point, pressure is extracted at approximately 50 PSI / min.
[0108] The thermal conductivity of the disclosed bacterial cellulose gels can be measured by known methods (see Hayase el al, App. Materials & Interfaces 6, 9466 (2014) and Zu el al, Chem. Mater. 30, 2759 (2018)). Figures 31A and 31B are thermal imaging photographs comparing a standard polysiloxane polymer (Figure 31A) to a gel formed by the disclosed method (Figure 31B). The patch of bacterial cellulose aerogel is cool compared to the surrounding heated surface.
[0109] While particular embodiments of the present disclosure have been illustrated and described, it would be obvious to those skilled in the art that various other changes and modifications can be made without departing from the spirit and scope of the disclosure. It is therefore intended to cover within the appended claims all such changes and modifications that are within the scope of this disclosure.
Claims
1. Aerogel containing bacterial cellulose.
2. about 10 -3 10. The aerogel of claim 1 having a thermal conductivity of from about 10 W / (m·K) to about 10 W / (m·K).
3. 10. The aerogel of claim 1 comprising nanocellulose.
4. About 1 Pa to about 10 6 2. The aerogel of claim 1 having a bulk modulus of 1.2 Pa.
5. 2. The aerogel of claim 1, wherein the bacterial cellulose is obtained from cellulose-producing bacteria.
6. 6. The aerogel of claim 5, wherein the bacterial cellulose is obtained from Acetobacter hansenii, Acetobacter xylinum, or a mixture thereof.
7. A film comprising bacterial cellulose nanomaterial.
8. The film of claim 7 having a thickness of about 1 μm to about 10 cm.
9. About 1 Pa to about 10 6 The film of claim 7 having a bulk modulus of 1.0 Pa.
10. 8. The aerogel of claim 7, wherein the bacterial cellulose is obtained from cellulose producing bacteria.
11. 8. The film of claim 7, wherein the bacterial cellulose is obtained from Acetobacter hansenii, Acetobacter xylinum, or a mixture thereof.
12. The film of claim 7 , wherein the nanomaterial comprises nanoribbons of a cellulosic material.
13. The film of claim 7 comprising fibrils of cellulosic material.
14. 8. The film of claim 7 comprising a layer comprising aligned nanoribbons of cellulosic material.
15. 15. The film of claim 14, wherein the nanoribbons have an aspect ratio of about 1:100 to about 1:1000.
16. 10. The film of claim 7 comprising a layer comprising aligned nanorods of cellulosic material.
17. 17. The film of claim 16, wherein the nanorods have an aspect ratio of about 1:10 to about 1:
100.
18. A composite structure comprising the film of any one of claims 7 to 17.
19. a) reducing the degree of binding between the growth medium, the bacteria, and optionally the cellulose fibrils; preparing a mixture of additives comprising: b) forming a thin film of bacterial cellulose; c) exchanging the water contained in the thin film with a solvent; d) drying the film to remove the solvent to form an aerogel; The method includes:
20. 20. The method of claim 19, further comprising treating the bacterial cellulose film to provide a bacteria-free film.
21. 20. The method of claim 19, wherein the additive reduces hydrogen bonding between fibrils in a bacterial growth medium.
22. The method of claim 21 , wherein the agent comprises a molecule that provides steric hindrance to interfibril bonds.
23. 20. The method of claim 19, wherein the bacterial cellulose is obtained from a cellulose-producing bacterium.
24. 20. The method of claim 19, wherein the bacterial cellulose is obtained from Acetobacter hansenii, Acetobacter xylinum, or a mixture thereof.
25. 20. The method of claim 19, further comprising manipulating the density of the fibrils by altering one or more of the growth medium and the nutrient composition within the growth medium.
26. 20. The method of claim 19, further comprising aligning the nanocellulose material within the dispersion.
27. 27. The method of claim 26, wherein the aligning step comprises subjecting the dispersion to a shear stress.
28. 27. The method of claim 26, wherein the aligning step comprises subjecting the dispersion to one or more of an electric field and a magnetic field.
Citation Information
Patent Citations
Cellulose-containing complex and its production, sugar compound and its production, resource recovery of paper, recycling waste paper into resource, and formed article and its production
JP2000313702A
Heat insulating sheet
JP2012062341A
Cellulose nanofiber and resin composition
JP2017115047A
Cellulose gels, films and composite materials containing the gels, and methods of forming same
JP2021528523A
Laminated glass, window glass for automobiles, and window glass for buildings
WO2017090686A1
